Water/cortical bone decomposition: A new approach in dual energy CT imaging for bone marrow oedema detection. A feasibility study. Issue 12 (December 2016) - Biondi, M.; Vanzi, E.; De Otto, G.; Banci Buonamici, F.; Belmonte, G.M.; Mazzoni, L.N.; Guasti, A.; Carbone, S.F.; Mazzei, M.A.; La Penna, A.; Foderà, E.; Guerreri, D.; et al.
Highlights: The use of water and cortical bone as base for DECT material decomposition is proposed. Clinical advantages can be possible by using water/cortical bone decomposition. Having resonance informations is still mandatory. Abstract : Introduction: Many studies aimed at validating the application of Dual Energy Computed Tomography (DECT) in clinical practice where conventional CT is not exhaustive. An example is given by bone marrow oedema detection, in which DECT based on water/calcium (W/Ca) decomposition was applied. In this paper a new DECT approach, based on water/cortical bone (W/CB) decomposition, was investigated. Materials and methods: Eight patients suffering from marrow oedema were scanned with MRI and DECT. Two-materials density decomposition was performed in ROIs corresponding to normal bone marrow and oedema. These regions were drawn on DECT images using MRI informations. Both W/Ca and W/CB were considered as material basis. Scatter plots of W/Ca and W/CB concentrations were made for each ROI in order to evaluate if oedema could be distinguished from normal bone marrow. Thresholds were defined on the scatter plots in order to produce DECT images where oedema regions were highlighted through color maps. The agreement between these images and MR was scored by two expert radiologists. Results: For all the patients, the best scores were obtained using W/CB density decomposition. Conclusions: In all cases, DECT color map images based on W/CB decomposition showed better agreement with MR in bone marrow oedema identification with respect to W/Ca decomposition. This result encourages further studies in order to evaluate if DECT based on W/CB decomposition could be an alternative technique to MR, which would be important when short scanning duration is relevant, as in the case of aged or traumatic patients.